Feature-oriented contract composition - Thüm, Thomas; Knüppel, Alexander; Krüger, Stefan; Bolle, Stefanie; Schaefer, Ina (The Journal of systems and software, 2019)
•Contract refinement in feature-oriented contract composition is seldom but crucial.•The Liskov substitution principle does not apply to features.•To handle the refinement of frames, techniques from OOP are sufficient. A software product line comprises a set of products that share a common code base, but vary in specific characteristics called features. Ideally, features of a product line are developed in isolation and composed subsequently. Product lines are increasingly used for safety–critical software, for which quality assurance becomes indispensable. While the verification of product lines gained considerable interest in research over the last decade, the subject of how to specify product lines is only covered rudimentarily. A challenge to overcome is composition; similar to inheritance in object-oriented programming, features of a product line may refine other features along with their specifications. To investigate how refinement and composition of specifications can be established, we derive a notion of feature-oriented contracts comprising preconditions, postconditions, and framing conditions of a method. We discuss six mechanisms to perform contract composition between original and refining contracts. Moreover, we identify and discuss desired properties for contract composition and evaluate which properties are established by which mechanism. Our three main insights are that (a) contract refinement is seldom but crucial, (b) the Liskov principle does not apply to features, and (c) it is sufficient to accommodate techniques from object-orientation in the contract-composition mechanisms for handling frame refinements.